Analysis of Poverty Determinants in the Eastern Region of Indonesia, 2001-2022 - Marcella, Rizka; Susilowati, Dwi (Faculty of Economics and Business, Jenderal Soedirman University, 2024)
Seen from the high poverty rate in Indonesia in 2022, it was found that provinces in the Eastern Indonesia Region (EIR) dominated the ten provinces with the largest percentages of poor population in Indonesia. Therefore, the purpose of this study is to determine the main aspects that affect the poverty rate in EIR. This research set the panel data regression analysis technique using six provinces in EIR as the unit of analysis or cross section data, as well as time series data from 2001-2022. Based on the research findings, the Minimum Wage had a negative influence and significant impact on the poverty rate; GRDP ADHK had a negative but insignificant effect on the poverty rate; and TPT had a positive and significant effect on the poverty rate; population had a negative and significant impact on the poverty rate, while the literacy rate had a positive but insignificant impact on the poverty rate. The five independent variables had a significant influence on the poverty rate in EIR